Microkinetic study of syngas conversion to dimethyl ether over a bifunctional catalyst: CZA/FER - Cho, Jiyeong; Park, Jongmin; Jung, Hyun Seung; Bae, Jong Wook; Na, Jonggeol; Lee, Won Bo; Park, Myung June (Korean Journal of Chemical Engineering, 2023)
Dimethyl ether (DME) is an environmentally friendly fuel and economical compound that can be synthesized through methanol (MeOH) dehydration or direct synthesis from syngas via the water-gas shift reaction. Catalysts such as Cu/ZnO/Al2O3 (CZA) for syngas conversion to MeOH and ferrierite (FER), a group of zeolites, or γ-Al2O3 for MeOH dehydration are necessary for these reactions. A hybrid catalyst, CZA/FER, can be used to directly convert syngas into DME via MeOH. While previous studies have developed kinetic models for these catalytic reaction systems using lumped or microkinetic models, differences in describing elementary reactions have led to variations in detail. In this study, we developed a microkinetic model for DME synthesis from syngas via MeOH over a CZA/FER hybrid bifunctional catalyst. We considered detailed reaction rates and site fractions to determine the dominance of DME synthesis path between the associative and dissociative paths. The model is based on a two-site fraction model for each catalyst, with 28 reactions over CZA and nine reactions over FER. Reaction parameters were determined using transition state theory (TST) and the UBI-QEP method for CZA and the second-order Møller-Plesset perturbation theory (MP2) for FER The pre-exponential factors of Arrhenius rate constants were estimated with experimental data at 250 °C which supported the model’s accuracy. Our results show that the associative pathway is dominant for DME synthesis over a CZA/FER hybrid catalyst, which differs from our previous research on microkinetic modeling for MeOH dehydration to DME over an FER zeolite. We also suggest an operating condition range for converting CO2 in the feed. We compared the relative reaction rates of elementary reactions and site fractions in each catalyst to enhance the understanding of the catalytic reaction system.
Keywords: C1 Chemistry; Dimethyl Ether; Hybrid Bifunctional Catalyst; Kinetic Modeling; Microkinetics